Building Integrity in Research: Indicators of Commitment to Scientific Ethics - Shehada, Mohammed A H; Nurabadi, Ahmad (Universitas Negeri Malang, 2024)
This article seeks to provide a comprehensive examination of the indicators of commitment to scientific ethics in research practices, the variability of these indicators across disciplines, the factors influencing ethical commitment, institutional strategies for monitoring integrity, and the role of training in fostering ethical adherence. By addressing these critical areas, the research will contribute to the ongoing discourse on enhancing ethical standards in scientific inquiry. The methodology for the article “Building Integrity in Research: Indicators of Commitment to Scientific Ethics” is designed to systematically explore the key indicators of adherence to scientific ethics in research practices. This section outlines the research design, data collection methods, analysis techniques, and ethical considerations that guided the study. the findings from this study highlight the importance of identifying key indicators of commitment to scientific ethics and understanding their variability across disciplines.